Variation in DNA-ploidy Levels of Reynoutria Taxa in the Czech Republic - Mandak, Bohumil; Pysek, Petr; Lysak, Martin; Suda, Jan; Krahulcova, Anna; Bimova, Katerina (Annals of botany, 2003)
The genus Reynoutria is represented by four taxa in the Czech Republic: Reynoutria japonica var. japonica, R. japonica var. compacta, R. sachalinensis and R. xbohemica. By using flow cytometry, cytological variability within the genus is described based on 257 Reynoutria samples. The varieties of R. japonica are cytologically uniform, var. japonica is exclusively octoploid (2n = 8x = 88) and var. compacta occurs only as a tetraploid (2n = 4x = 44), but R. sachalinensis and R. xbohemica exhibit some variation in chromosome numbers. Reynoutria sachalinensis is predominantly tetraploid (2n = 4 x = 44), but also occurs occasionally as hexaploid and octoploid cytotypes. The most common ploidy level in R. xbohemica is hexaploid (2n = 6x = 66), but tetraploid and octoploid clones were also found. The four taxa occurring in the Czech Republic are described briefly and the possible origins of the cytotypes discussed.
Keywords: Česká republika; Environment; DNA rostlinná; Czech Republic; Karyotyping; Polygonaceae; DNA, Plant; životní prostředí; Genetic Variation; ploidie; Ploidies; karyotypizace; genetická variace; chromozomy rostlin; Chromosomes, Plant